Influence of committees on earnings management - Palhares Felix, Carolina (2022)
The objective of this article was to verify whether the presence of the Audit Committee and the Board of Auditors encourages a migration from accrual-based earnings management to the management of real activities. The methodology used for the study development was empirical, quantitative and descriptive research. The data comprise Brazilian companies listed on B3 in the period from 2010 to 2017. The models were estimated by the ordinary least squares method - OLS - with panel data, controlled by year dummy and ADR. There is no evidence to indicate the presence of a trade-off. When there are audit committees and Board of Auditors, there is a decrease in both types of earnings management.